2021
DOI: 10.1111/tid.13772
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses to the SARS‐CoV‐2 BNT162b2 vaccine among a cohort of solid organ transplant recipients and healthy controls

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with increased morbidity and mortality in solid organ transplant (SOT) recipients. Despite exclusion from SARS-CoV-2 vaccine clinical trials, these individuals were identified as high-risk and prioritized for vaccination in public health guidelines. Methods:We prospectively evaluated humoral and cellular immune responses to two doses of the SARS-CoV-2 mRNA vaccine, BNT162b2, in 56 SOT recipients and 26 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Lack of accounting for cellular immunity is one way in which antibody measurements alone may not fully predict the clinical protectiveness of SARS‐CoV‐2 vaccination. Studies have shown decreased cellular immunity in SOTRs compared to healthy controls in response to SARS‐CoV‐2 vaccination 26,27 . However in these same studies, cellular and humoral immune responses did not correlate with each other, with some patients having a robust cellular immune response without a humoral response.…”
Section: Discussionmentioning
confidence: 85%
“…Lack of accounting for cellular immunity is one way in which antibody measurements alone may not fully predict the clinical protectiveness of SARS‐CoV‐2 vaccination. Studies have shown decreased cellular immunity in SOTRs compared to healthy controls in response to SARS‐CoV‐2 vaccination 26,27 . However in these same studies, cellular and humoral immune responses did not correlate with each other, with some patients having a robust cellular immune response without a humoral response.…”
Section: Discussionmentioning
confidence: 85%
“…The authors Yanis et al. correlated the humoral and cellular immune responses after two doses of COVID-19 mRNA vaccine in 56 SOT patients and 26 healthy individuals ( 29 ). In this study, four LuTx recipients were included, however, the majority of SOT types were kidney (41%) and liver (37%).…”
Section: Anti-covid-19 Vaccination In Lung Transplant Recipients: Fir...mentioning
confidence: 99%
“…We conducted testing for SARS‐CoV‐2 by detecting viral RNA in nasal specimens using reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) 8 and by detection of serum IgG to the SARS‐CoV‐2 spike and nucleocapsid proteins using enzyme‐linked immunosorbent assay (ELISA). 9 Those with negative RT‐qPCR results, but a positive ELISA within 4–6 weeks of symptom onset and no history of vaccination, were classified as SARS‐CoV‐2 positive. All data and laboratory results were maintained in a secure REDCap™ (Research Electronic Data Capture, Vanderbilt University) database.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory and blood specimens were transported to a VUMC research laboratory for storage and testing. We conducted testing for SARS‐CoV‐2 by detecting viral RNA in nasal specimens using reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) 8 and by detection of serum IgG to the SARS‐CoV‐2 spike and nucleocapsid proteins using enzyme‐linked immunosorbent assay (ELISA) 9 . Those with negative RT‐qPCR results, but a positive ELISA within 4–6 weeks of symptom onset and no history of vaccination, were classified as SARS‐CoV‐2 positive.…”
Section: Methodsmentioning
confidence: 99%